Partisan sorting in the United States, 1972–2012: New evidence from a dynamic analysis. (September 2015) - Lang, Corey; Pearson-Merkowitz, Shanna
Abstract: Whether Americans have "sorted" into politically like-minded counties and to what extent is hotly debated by academic and journalists. This paper examines whether or not geographic sorting has occurred and why it has occurred using a novel, dynamic analysis. Our findings indicate that geographic sorting is on the rise, but that it is a very recent phenomenon. In the 1970s and 1980s, counties tended to become more competitive, but by 1996 a pattern of partisan sorting had emerged and continued through the present. Results suggest this pattern is driven by Southern re-alignment and voting behavior in partisan stronghold counties. Lastly, we find evidence that migration can drive partisan sorting, but only accounts for a small portion of the change. Highlights: Estimate patterns of partisan sorting using county-level presidential voting outcomes. Partisan sorting has occurred, but is more recent than previous literature has suggested. Southern counties and one-sided counties drive the results. Voter migration also led to sorting, but accounts for a small part of total change.